Ultrasound to identify the lumbar space in women with impalpable bony landmarks presenting for elective caesarean delivery under spinal anaesthesia: a randomised trial. (December 2016) - Creaney, M.; Mullane, D.; Casby, C.; Tan, T.
Highlights: Ultrasound and palpation were compared to identify the insertion point for spinal anaesthesia in parturients with impalpable lumbar spines. Pre-procedural ultrasound significantly reduced the number of needle redirections. Pre-procedural ultrasound did not prolong overall procedural time. Abstract: Background: Ultrasound can facilitate neuraxial blockade in patients with poorly defined anatomical surface landmarks, but there are no studies comparing an ultrasound-guided technique with landmark palpation for spinal anaesthesia. The objective of this study was to compare pre-procedural lumbar ultrasonography with landmark palpation to locate the needle insertion point in women with impalpable lumbar spinous processes presenting for caesarean delivery. Methods: After institutional ethics committee approval, 20 women with impalpable lumbar spinous processes presenting for elective caesarean delivery were recruited. Patients were randomised to palpation or ultrasound. The primary outcome of the study was the number of needle passes to achieve lumbar puncture. Secondary outcomes were the overall procedural time and patient satisfaction score. Results: There was no difference in mean (±SD) body mass index of both groups (ultrasound 39.1 ± 5.02 kg/m 2 vs. palpation 38.3 ± 3.77 kg/m 2 ). There were significantly fewer needle passes in the ultrasound group (median 3 [IQR 1.8–3.2]) compared to the palpation group (median 5.5 [IQR 3.2–7.2] ( P =0.03)). More time was required to locate the needle insertion point in the ultrasound group (ultrasound 91.8 ± 30.8 s vs. palpation 32.6 ± 11.4 s, P <0.001). There was no difference in the total procedural time between groups (ultrasound 191.8 ± 49.4 s vs. palpation 192 ± 110.9 s, P =0.99). Conclusion: The use of ultrasonography to locate the needle insertion point reduced the number of needle passes in women with impalpable lumbar spinous processes undergoing elective caesarean delivery under spinal anaesthesia. Its use did not prolong overall procedural time.